Evaluation of the effect of T regulatory cell depletion and donor BCG vaccination on Mycobacterium tuberculosis H37Ra infection using an in vitro model of human PBMC infection. Issue 9 (11th November 2020) - Bhavanam, Sudha; Rayat, Gina R; Keelan, Monika; Kunimoto, Dennis; Drews, Steven J
Abstract: This study evaluated the effect of T regulatory cells (Treg cells) and the impact of BCG vaccination history of donors using an in vitro model of Mycobacterium tuberculosis H37Ra infection of peripheral blood mononuclear cells (PBMCs). PBMCs from donors with or without prior BCG vaccination were depleted of Treg cells (PBMCs-Tregs) or not depleted with Treg cells (PBMCs + Tregs) were infected up to 8 days with Mtb H37Ra. Cell aggregates were smaller in PBMCs-Tregs compared to PBMCs + Tregs at day 8 post-infection. Mtb CFUs were higher in the PBMCs-Tregs compared to PBMCs + Tregs at days 3, 5 and 8. The levels of IL-17, IFN-γ (at days 3 and 5), and TNF-α and IL-6 (at day 3) were lower in PBMCs-Tregs compared to PBMCs + Tregs. In contrast, the levels of IL-10 and IL-4 cytokines were higher at day 3 in PBMCs-Tregs compared to PBMCs + Tregs. BCG vaccination status of donors had no impact on the mycobacterial culture, level of cytokines and immune cell populations. This study shows that depletion of Tregs in human PBMCs infected with Mtb H37Ra in vitro leads to a shift from a Th1 to a Th2 cytokine rich environment that supports the survival of Mtb in this model. Abstract : T regulatory cells are important for the control of Mycobacterial growth in human peripheral blood mononuclear cells infected with Mtb H37Ra.